Effects of Temperature, Rainfall and Relative Humidity on Leaf Spot of Jackfruit Seedling and its Eco-friendly Management (The Agriculturists, 2012)
Experiments were carried out during 2005-08 to study the effect of weather prevalence of seedling diseases of jackfruit in different areas of Bangladesh and develop an environment friendly disease management practice. Leaf spot causal pathogen Colletotrichum gloeosporioides was identified. Incidence and severity of leaf spot at seedling stage were studied and significant variations were observed depending on weather factors. Occurrence of seedling diseases was significantly influenced by temperature, rainfall and relative humidity. Comparative effectiveness of BAU-biofungicide either alone or in combination with two fungicides viz. Cupravit and Bavistin were evaluated on jackfruit in the nursery. Among the treatments applied, Trichoderma harzianum based BAU-Biofungicide showed best result in controlling leaf spot disease. Keywords: Jackfruit seedling; leaf spot disease; ecofriendly management; BAU-Biofungicide DOI: http://dx.doi.org/10.3329/agric.v9i1-2.9487The Agriculturists 2011; 9(1&2): 126-136